Pengaruh Keterampilan Wirausaha dan Motivasi Berwirausaha terhadap Keberhasilan Usaha : Studi pada UMKM di Kota Medan - Andi Muharamen; Onan Marakali Siregar (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
MSME entrepreneurship is one aspect of local economic development while contributing to the employment network in Medan city. With the existence of MSMEs, they are able to contribute to regional economic development and reduce unemployment. However, in the process of running a business, there are obstacles for entrepreneurs, namely the lack of entrepreneurial skills and lack of motivation in entrepreneurship which can affect the success of MSMEs. This study aims to determine the effect of entrepreneurial skills and entrepreneurial motivation on business success in MSMEs in Medan city. The form of research used is quantitative with an associative approach. The population in this study were MSMEs in Medan City. With a sample of 100 respondents, the sample approach used in this study was non-probability sampling in the form of purposive sampling. Primary data obtained through direct distribution of questionnaires and secondary data obtained through literature studies. The results of this study indicate that entrepreneurial skills have a significant positive effect on business success, obtained a tcount value of 4.420> 1.984 with a sig value of 0.001 <0.05 and has a regression coefficient value of 0.325. Entrepreneurial motivation also has a significant positive effect on business success, obtained a tcount value of 2.680> 1.984 with a sig value of 0.009 <0.05 and has a regression coefficient value of 0.235. In simultaneous testing of entrepreneurial skills and entrepreneurial motivation variables simultaneously affect the level of influence of 49.7% while the remaining 50.3% is influenced by factors outside this study.